Pengaruh Model Problem Based Learning (PBL) berbantuan mind map terhadap kemampuan berpikir kritis siswa - Firdyan, Lingga Zuama; Soekamto, Hadi; Insani, Nailul; Wirahayu, Yuswanti Ariani (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2023)
Studying geosphere phenomena in geography learning requires student learning activities with scientific steps. The mind map-assisted PBL model is a scientific model that is centered on students with the study of problem phenomena. The mind map on the model serves as a tool to facilitate student learning. Critical thinking skills are students' abilities in formulating problems, arguing, concluding, evaluating, and providing solutions on essay tests. This study aimed to see the effect of the mind map-assisted PBL model on students' critical thinking skills. The method used was a quasi-experimental posttest-only control group design which was carried out at SMAN 10 Malang City in the odd semester of 2022/2023. The study subjects were XI IPS 1 control class and XI IPS 2 experimental class. Research trials were conducted to see the validity and reliability of the tool. Instruments using SPSS 25 are declared valid and reliable. Data were analyzed using the normality test and homogeneity test. The second test was declared normal and homogeneous with a value of 0.077 and 0.423, respectively in the experimental class. Meanwhile, the hypothesis test has acceptable H1 results, which means that the PBL model assisted by mind maps influences students' critical thinking skills. The results of critical thinking scores in the experimental and control classes were 80.44 and 72.62 with different scores for each indicator. Another finding from this research is that gender also found differences in critical thinking skills. Kajian fenomena geosfer dalam pembelajaran geografi memerlukan aktivitas belajar siswa dengan langkah-langkah saintifik. Model PBL berbantuan mind map merupakan model saintifik yang berpusat pada siswa dengan kajian fenomena masalah. Mind map pada model berfungsi sebagai sarana dalam memudahkan siswa belajar. Kemampuan berpikir kritis merupakan kemampuan siswa dalam merumuskan masalah, berargumen, menyimpulkan, evaluasi, dan memberi solusi pada tes essay. Tujuan penelitian ini adalah untuk melihat pengaruh model PBL berbantuan mind map terhadap kemampuan berpikir kritis siswa. Metode yang dipergunakan yaitu eksperimen semu desain posttest-only control group yang dilaksanakan di SMAN 10 Kota Malang semester ganjil 2022/2023. Subjek dari penelitian yaitu XI IPS 1 kelas kontrol dan XI IPS 2 kelas eksperimen. Data dianalisis menggunakan uji normalitas dan uji homogenitas. Kedua pengujian dinyatakan normal dan homogen dengan masing-masing nilai sebesar 0,077 dan 0,423 pada kelas eksperimen. Sedangkan uji hipotesis memiliki hasil H1 dapat diterima yang berarti model PBL berbantuan mind map memberikan pengaruh pada kemampuan berpikir kritis siswa. Hasil nilai berpikir kritis pada kelas eksperimen dan kontrol sebesar 80,44 dan 72,62 dengan skor tiap indikator yang berbeda-beda. Temuan lain dari penelitian ini yakni gender juga mencari perbedaan terhadap kemampuan berpikir kritis.